Education: the best inheritance. Educational decisions and expectations of parents. An empirical approach. Juan Ansión, Alejandro Lazarte, Sylvia Matos, José Rodríguez, Pablo Vega-Centeno - Montero, Carmen (1999)
The review does not present a summary.